Hyperbaric oxygen in animal model of rheumatoid arthritis: Analysis of HIF-1α, ACPA and IL-17a - Titut Harnanik; Sapta Prihartono; Tedy Juliandhy (MDPI AG, 2020)
Antigen and collagen-induced arthritis (ACIA) is animal model of rheumatoid arthritis. The aim of this study was to identify the effect of different doses of hyperbaric oxygen (HBO) exposure in reducing inflammation on ACIA through analysis hypoxia inducible factor-1α (HIF-1α), anticyclic citrullinated peptide antibody (ACPA) and interleukine 17a (IL-17a). 24 male Balb/C mice were divided into 3 groups, 8 mice did not receive HBO exposure as a control group (G1) and 16 mice received HBO exposure as treatment group (G2 and G3). G2 was ACIA which was exposed to HBO 2.4 ATA O2 100% 90 minutes divided by 3 each 30 minutes intervals 2 times 5 minutes breathing with normal air for 10 consecutive days. G3 was ACIA which was exposed to HBO 2.4 ATA O2 100% 90 minutes divided by 3 each 30 minutes intervals 2 times 5 minutes breathing with normal air for 5 consecutive days, break 5 days, 5 consecutive days. ACPA and IL-17a were measured by enzyme-linked immunosorbent assay (ELISA) technique. The expression of HIF-1α was measured by immunohistochemistry technique. There was significant decrease of ACPA levels, IL-17a levels and HIF-1α expression (P< 0.05) in G2 and G3 compared to G1. There was not significant decrease of ACPA levels (P> 0.05), there was significant decrease of IL-17a levels and HIF-1α expression (P<0.05) in G2 compared to G3. G2 was a group with a higher oxygen partial pressure than G3. HBO 2.4 ATAO2 100% 90 minutes divided by 3 each 30 minutes intervals 2 times 5 minutes breathing with normal air for 10 consecutive days more effective in reducing inflammation than exposure 5 consecutive days, break 5 days, 5 consecutive days in ACIA. HBO has therapeutic potential for the treatment of RA.